Implementasi Metode Pembelajaran Kuis Interaktif untuk Meningkatkan Hasil Belajar Siswa di Kelas X-4 SMAN 2 Karawang - Muhammad Fikri Ramadhan; Muhammad Rizal Arif; Nurjannah , Nurjannah; Nur Siti Rahmayanti; Putri Khoerunnisa (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to help students better understand the historical material about the entry of Islam into Indonesia by using the interactive quiz method in class X-4 SMAN 2 Karawang. The background is the low understanding and participation of students in history lessons, which so far still use conventional methods such as lectures. The study was conducted in two cycles through the stages of planning, implementation, observation, and reflection. Data were collected through observation, comprehension tests, and student response questionnaires. The results showed a significant increase in student understanding, both from the test results and their activeness in class. Students also looked more enthusiastic, motivated, and able to understand the material better. In conclusion, the interactive quiz method has proven effective in improving student understanding and engagement, and can be an attractive option for teachers to create a more lively and enjoyable learning atmosphere.